ANALISIS FAKTOR LOYALITAS SUPORTER AREMA - Emmanuel Luika (Parsimonia - Jurnal Ekonomi dan Bisnis, 2017)
This research aims to analyze the influence of cognitive antecedents factor, player factor, pure entertainment value, fan bonding, motivation, emotional intelligence (ESQ), aggressive behavior, environment, confidence, centrality, Clarity), tradition and history, authenticity to the loyalty of Arema soccer fans and to know the factors that have dominant influence on the loyalty of Arema soccer fans. This research is a descriptive quantitative research using Principal Component Analysis (PCA), data analysis technique from PCA resulted in factor loading and grouping of several variables, supported by Classical Assumption Test, and Multiple Linear Regression Analysis which produced the most influential either Partial or simultaneous. This study used a sample of 200 respondents. The results of this study indicate that the components that simultaneously affect the loyalty of Arema supporters are Component 1 (Internal), Component 2 (Entertainment), component 3 (Believe), and Component 4 (External). While component 1 (Internal) consisting of Fan Bonding, Emotional Intelligence, Cognitive anticedent, Centering, and Playing Factor are the components that most influence (partially, most significantly) Arema supporter loyalty. This research can provide suggestions for the company can maintain and improve service between komponen 1 consisting of Fan Bonding, emotional intelligence, Cognitive anticedent, because kompenen 1 most dominant influence Loyalitas Suporter Arema, so Loyalitas Suporter Arema will increase and keep this loyalty can be done with a variety of activities that are more emphasized in the routine or activities carried out routine and centered in a place.